Navigating Digital Disruption: Professional Competence of Lower Primary Teachers in the Merdeka Curriculum for Alpha Generation Learners - Nisrina Ajrina Nur Hidayah (Global Education Journal, 2026)
The rapid acceleration of digital disruption has significantly transformed elementary education, particularly in relation to the learning characteristics of Generation Alpha and the implementation of Indonesia’s Merdeka Curriculum. In this context, lower primary teachers are required to possess adaptive professional competencies that integrate pedagogical expertise, digital literacy, and ethical awareness. This study aims to explore the professional competence of lower-grade elementary teachers in responding to digital disruption during the implementation of the Merdeka Curriculum for Generation Alpha learners, as well as to identify supporting and constraining factors influencing this competence. Employing an exploratory qualitative approach, the study involved nine lower-grade teachers from an Islamic elementary school in Yogyakarta selected through purposive sampling. Data were collected using open-ended online questionnaires and analyzed through thematic analysis. The findings reveal that teachers strongly recognize Generation Alpha as digital native learners and acknowledge digital competence as a core component of professionalism. This study concludes that strengthening teachers’ digital pedagogical competence through continuous, context-based professional development is essential for effective curriculum implementation. The study contributes to the literature by providing empirical insights into lower primary teacher professionalism within digital transformation and curriculum reform contexts.